Expressed preferences for public health education of students during COVID-19 vaccination intervention: a cross-sectional comparative study - Debendra Nath Roy; Md.Shah Azam; Ekramul Islam (Springer, 2024)
Abstract Background Public health education is a powerful tool for improving communicable disease awareness and prevention protocols. Despite the fact that health education is crucial for the advancement of COVID-19 awareness and vaccination decisions, how a teacher approaches students to learn about health education during COVID-19 vaccination is  a challenging issue. This study aimed to assess the preferences for public health education during COVID-19 vaccination intervention and compare the predictors of preferences between science and non-science university students in Bangladesh. Methods A multi-item questionnaire was developed and an online link was conveniently sent to the encounters between 31st May, 2023 and 15th August, 2023. Binary logistic regression analysis was applied to rationalize the research objective. Results The pooled preference for public health education was 71.3% (95% Confidence Interval [CI] 67.7-74.3) vs. 81.5% (95% CI 79.3-84.7) between science and non-science students. Out of twelve predictors "vaccine agreement", "bio-safety behavior", and "disease awareness" were significantly associated (p < 0.01, p < 0.05) with the preference for public health education in both groups. Varied effects were also observed for some predictors: vaccine "safety" and "side effects" were significant (p < 0.05, p < 0.01) in science and non-science students, respectively. To address the conflict in decisions, non-science students significantly preferred "prevention alliance" whereas science students preferred "environmental health" issues (p < 0.05). Conclusion Public health education was more preferred by non-science university students than by science students in making COVID-19 vaccine decisions . The focus of transformative public health education should be interdisciplinary, including information on communicable diseases, public health measures, and prevention alliances, as well as information about vaccines' side effects and safety.